EFEKTIVITAS UNICEF COUNTRY PROGAMME 2009-2013 DALAM MEMBANTU PEMERINTAH UNTUK MELINDUNGI HAK ANAK PASCA PERANG SIPIL I DI CÔTE D’IVOIRE - Widyawati, Donata Asdar; Windiani, Reni (Journal of International Relations, 2019)
This research was motivated by economic pressures, domestic political upheaval, and military coups which ignited the emergence of the First Civil War that occurred in 2002-2008. The civil war indirectly forced the residents of Côté d’Ivoire to take part in it and get the effects of the civil war, one of which was the abandonment of the protection of children's rights from the Côté d’Ivoire Government due to the civil war. The United Nations Children's Fund (UNICEF), as an international organization that focuses on upholding and protecting the rights of children and women, provided the Country Programme 2009-2013 to help protect the rights of children and women in Côté d’Ivoire. The purpose of this study is to determine the level of effectiveness in achieving the aid program. With the help of the concept of effectiveness and international organizations, the authors analyzed the effectiveness of the UNICEF Country Programme 2009-2013, which produced research findings, that UNICEF Country Programme 2009-2013 has been effective in assisting the Côté d'Ivoire Government to fulfill, enforce and protect children's rights in Côté d'Ivoire.